2020
DOI: 10.1371/journal.pone.0239775
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of essential oils from Ethiopian thyme (Thymus serrulatus and Thymus schimperi) against tooth decay bacteria

Abstract: In this study, we evaluated the antibacterial activities of the essential oils (EOs) of Thymus serrulatus and Thymus schimperi collected from Ofla (Ofl), Alamata (Ala), Yilmana Densa (Yil), Tarmaer (Tar), Butajira (Buta), and Bale (Bal) in Ethiopia against cariogenic bacteria (Streptococcus mutans and Lactobacillus) isolated from human teeth. Inhibition zones (IZs), minimum inhibitory concentrations (MICs), and minimum bactericidal concentrations (MBCs) were measures of the antibacterial activity. Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Among 79 EsO screened for antibiofilm ability and reducing virulence of the uropathogenic strains of Escherichia coli, thymol‐rich Thymus vulgaris oil and carvacrol‐rich Origanum vulgare oil as well as their major constituents, carvacrol and thymol, inhibited this pathogenic microorganism significantly ( Lee et al, 2017 ). EsO of the Ethiopian Thymus serrulatus and Thymus schimperi containing thymol and carvacrol as the major components demonstrated the significantly high inhibition zones against tooth decay bacteria Streptococcus mutans and Lactobacillus ( Damtie et al, 2020 ). Thymol (55.35%) and p- cymene (11.2%) were the major components of the EsO hydrodistillated from the Turkish Thymus vulgaris .…”
Section: Discussionmentioning
confidence: 99%
“…Among 79 EsO screened for antibiofilm ability and reducing virulence of the uropathogenic strains of Escherichia coli, thymol‐rich Thymus vulgaris oil and carvacrol‐rich Origanum vulgare oil as well as their major constituents, carvacrol and thymol, inhibited this pathogenic microorganism significantly ( Lee et al, 2017 ). EsO of the Ethiopian Thymus serrulatus and Thymus schimperi containing thymol and carvacrol as the major components demonstrated the significantly high inhibition zones against tooth decay bacteria Streptococcus mutans and Lactobacillus ( Damtie et al, 2020 ). Thymol (55.35%) and p- cymene (11.2%) were the major components of the EsO hydrodistillated from the Turkish Thymus vulgaris .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that essential oils from Thymus schimperi exhibited promising antimicrobial activities. 96 , 97 In silico screening of lead compounds from food promote the therapeutic role of food in combating the COVID-19 pandemic. 98 As the top hits in this study exhibited excellent binding and acceptable ADMET properties, further studies are recommended to optimize these compounds in the plant to design drugs tackling respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…EOs of Thymus serrulatus and Thymus schimperi were shown to possess strong antibacterial activity against Lactobacillus and S. mutans , with higher contents of thymol and carvacrol compounds reported to be the cause of this inhibition [ 79 ]. Similarly, EOs have been isolated from various parts of Eugenia caryophylata , such as the buds, leaves, and stems, with the main components being eugenol, β-caryophyllene, and eugenyl acetate.…”
Section: Antimicrobial Efficacy Of Eosmentioning
confidence: 99%